MODIFIKASI PADA SALURAN TRANSISI PELIMPAH BENDUNGAN UNTUK MENGURANGI TERBENTUKNYA ALIRAN SILANG DI SALURAN PELUNCUR (Studi Kasus : Model Bendungan Bener) - , Akmal; , Prof. Ir. Djoko Legono, Ph.D, ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Before having it functioned for irrigation purposes as well as to provide potable water and electric power generator, a preliminary plan by constructing the Bener Weir is required. The weir is situated on Bogowonto River within the administration boundaries of the Purworejo Regency. As an expensive structure, the weir should be safe and able to fulfill the required water volume as planned. It is also required that the spillway structure should be able to pass the planned flood discharge. To support its operation, modeling is required. Such modeling was carried out within 1:100 scale, in the Hydraulic Laboratory of the Civil and Environmental Engineering of Gadjah Mada University. In order to obtain a design that fulfill the hydraulic condition, several experiments were taken to the original design, as the Model Seri 0, which was a model based on a design made by plan consultant. The Model Seri 0 was used to identify the hydraulic phenomenon of the building within various operation discharge. Based on the Experiment Model Seri 0, unfavorable result was obtained. The problem was the occurrence of cross flow in the chuteway channel resulted from the turning of the flow by the vertical wall in front of the spillway. Thus, the flow in the transition channel was distributed unevenly and this condition was continued to the chuteway channel. The experiment was developed by positioning the baffle block on the end of the transition channel in the experiments for the 3 model series: Model Seri 1, Model Seri 2, and Model Seri 3. This was expected to improve the flow fluctuation and decrease the cross flow in the chuteway channel. The measurement of the flow depth along the chuteway channel used the Capacitive Sensor assembled in special form. The experiment results on Model Seri 0 showed significant difference between the maximum and minimum height of the water surface in the section, which was Îhmax = 0,816 cm. The experiment in the model serial using the baffle block showed varied result on the flow distribution. The experiment for Model Seri 1 insignificantly decreased the Îhmax to 0,775 cm with flow condition containing cross flow. The application of Model Seri 2 with transformation of shape, dimension and positioning pattern of baffle block have given better result by decreasing Îhmax. The difference of water surface height in the Experiment of Model Seri 2, was Îhmax = 0,557 cm. The subsequent experiment, which was Experiment of Model Seri 3, was carried out by adding one row of baffle block on the upstream to become 3 rows. The shape and dimension of the baffle block in the Experiment of Model Seri 3 were the same as the Experiment of Model Seri 2. The result of the flow depth measurement along the chuteway channel in the Experiment of Model Seri 3 showed preferable result as indicated by more uniform flow distribution that the cross flow was not too visible with Îhmax = 0,436 cm. The experiment result of each model Seri indicated that the best design resulted from Experiment of Model Seri 3 as the final design.